Uncertain Systems Order Reduction by Aggregation Method - Bogapurapu Gayatri; Kalyana Kiran Kumar; Akella Venkata Santosh Lakshmi; Vyakaranam Sai Karteek (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In the field of control engineering, approximating the higher-order system with its reduced model copes with more intricate problems. These complex problems are addressed due to the usage of computing technologies and advanced algorithms. Reduction techniques enable the system from higher-order to lower-order form retaining the properties of former even after reduction. This document renders a method for demotion of uncertain systems based on State Space Analysis. Numerical examples are illustrated to show the accuracy of the proposed method.